The solution of the equation is x = -4/3.
<h3>What does it mean to solve an equation?</h3>
An equation represents equality of two or more mathematical expression.
Solutions to an equation are those values of the variables involved in that equation for which the equation is true.
WE have been given an equation as;
|x - 4| = 5x + 12
In an absolute value equation, we solve the original expression as our first equation. Our second one is that we multiply the right side by -1.
Case 1: original equation
|x - 4| = 5x + 12
x - 4 = 5x + 12
x - 5x = 12 + 4
-4x = 16
x = -4
Case 2: Opposite equation
|x - 4| = 5x + 12
x - 4 = - (5x + 12)
x - 4 = - 5x - 12
x + 5x = -12 + 4
6x = -8
x = -4/3
Now we have two solutions. We need to check for extraneous solutions because of all the manipulations;
Check:
|x - 4| = 5x + 12
use x = -4
|-4 - 4| = 5(-4) + 12
| -8 | = -20 + 12
8 = -8
Thus, it is Not a solution
Now, |x - 4| = 5x + 12
use x = -4/3
| -4/3 - 4| = 5( -4/3) + 12
|-16/3 | = -20/3 + 12
|-16/3 | = 16/3
16/3 = 16/3
Thus, it is the Solution.
Learn more about solving equations here:
brainly.com/question/18015090
#SPJ1
Answer:
Sample Response: First, the like terms had to be combined using the lowest common denominator (LCD). Then the subtraction property of equality was used to isolate the variable term. Finally, both sides of the equation were multiplied by the reciprocal of the coefficient to solve for a.
Step-by-step explanation:
Answer:
8
Step-by-step explanation:
2
235.24 + 45.58 = 280.82
280.82/2 = 140.41
each check was for $140.41
Answer: y = 1/3 x - 2
Step-by-step explanation: